KONVERGENSI KURIKULUM MERDEKA BELAJAR KAMPUS MERDEKA DAN TANTANGAN KEILMUAN PROGRAM STUDI PENDIDIKAN BAHASA INGGRIS FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN - Yurnalis, Beniario (Inovasi Pendidikan, 2022)
Curriculum changes are marked by the start of the design of a new order and the imagination of the future interpreted as the implementation of the flagship program provided by each study program. This design has been implemented with a curriculum change policy. In order to improve the quality of graduates in accordance with the needs of the world of work and are highly absorbent. These synergies include the Kampus mengajar program had been hotly discussed recently. However, it is not uncommon to experience boredom to find convergence between policy and scientific challenges. Various studies related to curriculum convergence have been delivered in the form of seminars, Conferences, research journals such as Giri. Efraim Ferdinand, (2008), Fuadi Marja Tuti, Fauzi. Imron. (2020). Irianto. April, et al. (2021). However, very few have discussed how the convergence of profiles of graduates from the English Education Study Program towards campus teaching programs is related to the relevance of curriculum development principles and the challenges in participating in the MBKM program, especially for students.This research was conducted by conducting interviews and reviewing the final project documents for Kampus Mengajar participants. The validity of the data was carried out by means of semantic validity and peer testing in order to obtain valid and reliable data. The findings of this study are the convergence of the curriculum with the campus teaching program in the English education study program which is constructed on the profile of the main graduates, namely as prospective educators not as additional profiles, then recognized into the conversion of relevant courses.while the challenge is that the implementation of this program should have additional coaching on materials. Teaching English in elementary schools for students as part of developing English courses for specific purposes.